Advancing gender equality through voluntary sustainability systems: From commitments to action - Centre for Responsible Business (2024)
This webinar explores ways to move from commitments to action on gender equality. Drawing on a new toolkit and other key resources that can support movement in this area, the session contributors will present concrete ways they are addressing gender equality in their: 1) organization; 2) standards; 3) programming; and 4) monitoring, evaluation, learning, and impact assessments (MELIA). Different VSS across sectors will share critical reflections, opportunities, challenges, and experiences with these approaches and strategies, and the promise they have shown for advancing gender equality in market systems.